2008
DOI: 10.1111/j.1365-3083.2008.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategy to Assess the Overall Cytokine Profile of Circulating Leukocytes and its Association with Distinct Clinical Forms of Human Chagas Disease

Abstract: Herein we have employed an alternative strategy to assess the cytokine patterns of circulating leukocytes and correlate dominant cytokine profiles with indeterminate‐IND and cardiac‐CARD clinical forms of Chagas disease. We have first calculated median percentages of cytokine‐positive leukocytes of our study sample to establish, for each cytokine‐positive cell population, the cut‐off edge that would segregate ‘low’ and ‘high’ cytokine producers to build colour diagrams and draw a panoramic cytokine chart. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 26 publications
7
64
0
3
Order By: Relevance
“…Moreover, monocytes play an important role in the activation of the innate response during the early stages of infection by mediating the cross-talk between the innate and the adaptive immune responses 23 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 99%
“…Moreover, monocytes play an important role in the activation of the innate response during the early stages of infection by mediating the cross-talk between the innate and the adaptive immune responses 23 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 99%
“…Likewise, Araú jo et al [9] showed that IND individuals have higher levels of CD4+CD25 high lymphocytes expressing FoxP3 and IL-10, compared to individuals with CARD. Moreover, VitelliAvelar et al [10] showed a pattern production of regulatory cytokines produced by PBMC from IND patients, contrasting with a profile of inflammatory cytokine production in CARD patients.…”
mentioning
confidence: 99%
“…This profile may be useful to limit parasitemia and confine infection to tissues. In fact, it has been demonstrated that NK cells are important in defense against the spread of parasitic infection (Brener & Gazzinelli, 1997), and are an important source of INF-a key cytokine to activate macrophages and help with parasite clearance (Camargo, et al, 1997 Gomes, et al, 2003) while in CCC patients they produce more TNF- (Vitelli- Avelar, et al, 2008), leading to a proinflammatory profile that could be responsible for chronic myocarditis. Toll-like receptors (TLR) are also implied in the response to acute infection with T. cruzi.…”
Section: Innate Immunitymentioning
confidence: 99%